Management of adults with Wilms'' tumor: recommendations based on international consensus. Issue 7 (July 2011) - Segers, Heidi; van den Heuvel-Eibrink, Marry M; Pritchard-Jones, Kathy; Coppes, Max J; Aitchison, Michael; Bergeron, Christophe; de Camargo, Beatriz; Dome, Jeffrey S; Grundy, Paul; Gatta, Gemma; Graf, Norbert; Grundy, Paul; et al.
Since Wilms'' tumor occurs rarely in adults, there are no standard treatments available. Most adult patients will be diagnosed unexpectedly following nephrectomy for presumed renal cell carcinoma. Outcome for adults is inferior compared with children, although better results are reported when treated within pediatric trials. Multiple factors, including the unfamiliarity of adult oncologists and pathologists with Wilms'' tumors, lack of standardized treatment and consequent delays in initiating the appropriate risk-adapted therapy, may contribute to the poor outcome. A standardized approach for the management of adult Wilms'' tumors is proposed with the aim to limit treatment delay after surgery and encourage a uniform approach for this rare disease and thereby improve survival. These recommendations are based on discussions held with representatives of the renal tumor committees of the Society of Paediatric Oncology and Children''s Oncology Group, and have been updated with a review of more recently published institutional and trial experience of adults treated on pediatric protocols. They provide a critical evaluation of the current evidence for the management of adult Wilms'' tumors and propose details of how current pediatric therapeutic guidelines could be adapted for use in adults.